PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP NIAT PEMBELIAN ULANG PRODUK ERIGO - Wijaya, Aditya Hadi; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The increasingly advanced economic development in Indonesia has an impact on various types of businesses and businesses, one of which is the clothing or fashion business. Fashion itself is a type of business that places clothing products as its business axis. This study aims to determine the influence of brand image, product quality, and promotion on product repurchase intention. This type of research is explanatory research which explains and proves the relationship and influence between the independent and dependent variables. This study used a sample of 100 respondents and the distribution of the questionnaire was carried out in online media and groups concerned with Erigo products using the help of google forms. Sampling using random sampling method (random sampling). The sample consists of male and female respondents who are at least 15 years old and have used or purchased Erigo products. Data analysis using Multiple Linear Regression Analysis using SPSS ver. 25. The results of the analysis obtained in this study are brand image, product quality and promotion have a significant effect on repurchasing intention.